THE QUALITY OF CHILLED RAM SEMEN AFTER STORAGE IN EXTENDER WITH ADDITION OF MELATONIN AT 4 C - Triyaningrum, Triyaningrum; Fahrudin, Mokhamad; Karja, Ni Wayan Kurniani; Prasetyaningtyas, Wahono Esthi (Jurnal Kedokteran Hewan, 2024)
Semen was collected using an artificial vagina, and then examined macroscopically and microscopically. Semen with motility of 70% was diluted into different extenders: tris egg yolk-glucose (TEYG), tris egg yolk-glucose extender with 0.5 mM melatonin (TEYG + M0.5), tris egg yolk-glucose extender with 1 mM melatonin (TEYG + M1), tris egg yolk-glucose extender with 2 mM melatonin (TEYG + M2). All semen samples were stored at 4 C for 5 days (H0-H5) and examined every 24 hours. Semen was examined for spermatozoa motility, viability, abnormality, and membrane plasma integrity. The results showed that there were no significant changes of semen quality on H0 (P0.05). In general, the melatonin supplemented groups had a higher semen quality value than the control. Melatonin supplementation can protect and maintain the quality of chilled semen. In addition, the result showed that TEYG + M1 extender was the best extender treatment, which was indicated by higher values than other treatments.